Power of a Power

šŸ†Practice power of a power

Power of a Power

When we have an expression raised to a power that, in turn, is raised (within parentheses) to another power, we can multiply the exponents and raise the base number to the result of this multiplication.

Formula of the property

(an)m=a(nƗm) (a^n)^m=a^{(n\times m)}
This property is also concerning algebraic expressions.

Start practice

Test yourself on power of a power!

einstein

Insert the corresponding expression:

\( \left(10^3\right)^3= \)

Practice more now

A - When there is a power inside parentheses.

Power of a power basic examples

Example 1

(43)2=(4^3 )^2=
We can see that the exponent 2 2 applies to the entire expression 43 4^3 .
therefore, we can multiply both exponents and raise the base to the result of the multiplication.
We will obtain:
43Ɨ2=46=4096 4^{3\times2}=4^6=4096


If we were presented with an exercise in which there is a certain power over a term that already has another power, we will multiply the powers that have equal bases.

Example 2

Let's start with an easy one:

(X6āˆ’3)4= (X^{6-3})^4=

We'll see that there is a subtraction in the exponents of X X and that, first, we must deal with it.

We'll do this and obtain:

(X3)4= (X^3)^4=

Now we can apply the power of a power property and multiply the exponents, we will obtain:

X12 X^{12}


Good. Let's move on to a more complicated example:

Example 3

(2X2X)4ā‹…(4Y2Y)3= (\frac{2X^2}{X})^4\cdot(\frac{4Y^2}{Y})^3=

Recommendation:

Before applying the power located outside the parentheses to each of the terms separately, first, it is advisable to carefully observe the exercise.

Upon observing it, you will realize that you can reduce or subtract exponents from the fractions themselves, before touching the exponent located outside the parentheses.

We will subtract the exponents of the corresponding bases (we will reduce) and obtain:

(2X)4ā‹…(4Y)3= (2X)^4\cdot(4Y)^3=

Now we can apply the exponent to each of the terms separately (do not forget about the coefficients) and we will get:

16X4ā‹…64Y3= 16X^4\cdot64Y^3=

We can try to find a common term to better organize the exercise and we will obtain:

16(X4ā‹…4Y3) 16(X^4\cdot4Y^3)


Perfect! Now, let's move on to a complex and slightly different example:

Power of a power advanced examples:

Example 4

(2X+3)Xā‹…(2X)4= (2^{X+3})^X\cdot(2^X)^4=

Don't worry, even if there are mathematical operations among the exponents, the properties do not change.

Let's start with the first expression which is a bit more complex. We learned that, when we have a power of a power we multiply the exponents.

We will multiply the entire exponent that is inside the parentheses by the entire exponent located outside the parentheses. We will do the same with the other term and we will obtain:

2(X+3)ā‹…Xā‹…24X= 2^{(X+3)\cdot X}\cdot2^{4X}=

We will multiply the exponents of the first expression and we will obtain:

2X2+3Xā‹…24X= 2^{X^2+3X}\cdot2^{4X}=

Now let's remember that, if we have a multiplication operation between equal bases we can add the exponents.

We will do this and we will obtain:

2X2+3X+4X= 2^{X^2+3X+4X}=

We simplify terms in the exponent and it will give us:

2X2+7X= 2^{X^2+7X}=


Example 5

Simplify the following expression:

(3x3y2)2(2x2y4)4(2xy2)3 \frac{\left(3x^3y^2\right)^2\left(2x^2y^4\right)^4}{\left(2xy^2\right)^3}

To simplify the expression, first apply the power of a product property, which allows us to raise each of the factors inside the parenthesis to the indicated power, then apply the power of a power property. We obtain:

(32(x3)2(y2)2)ā‹…(24(x2)4(y4)4)23(x)3(y2)3=(9x6y4)ā‹…(16x8y16)8x3y6 \frac{\left(3^2\left(x^3\right)^2\left(y^2\right)^2\right)\cdot\left(2^4\left(x^2\right)^4\left(y^4\right)^4\right)}{2^3\left(x^{}\right)^3\left(y^2\right)^3}=\frac{\left(9x^6y^4\right)\cdot\left(16x^8y^{16}\right)}{8x^3y^6}

Finally, apply the properties of products and quotients of powers with the same base:

144x6+8y4+168x3y6=114x14y208x3y6=18x14āˆ’3y20āˆ’6=18x11y14 \frac{144x^{6+8}y^{4+16}}{8x^3y^6}=\frac{114x^{14}y^{20}}{8x^3y^6}=18x^{14-3}y^{20-6}=18x^{11}y^{14}


Exercises on Power of a Power

Basic Exercises of Power of a Power:

(42)2= \left(4^2\right)^2=

(33)2= \left(3^3\right)^2=

(22)2= \left(2^2\right)^2=

(52)5= \left(5^2\right)^5=

(72)2= \left(7^2\right)^2=


Exercises of Power of a Power:

(X2āˆ’4)2= \left(X^{2-4}\right)^2=

(X2+4)3= \left(X^{2+4}\right)^3=

(X21āˆ’7)2= \left(X^{21-7}\right)^2=

(X11āˆ’9)3= \left(X^{11-9}\right)^3=

(X5āˆ’3)3= \left(X^{5-3}\right)^3=


Intermediate Level Power of a Power Exercises

(4X5X)2ā‹…(3Y3Y)3= (\frac{4X^5}{X})^2\cdot(\frac{3Y^3}{Y})^3=

(4Y52Y)2ā‹…(Y42Y)4= (\frac{4Y^5}{2Y})^2\cdot(\frac{Y^4}{2Y})^4=

(2X52X)3ā‹…(X32X)3= (\frac{2X^5}{2X})^3\cdot(\frac{X^3}{2X})^3=

(2Y52Y5)3ā‹…(X32X3)3= (\frac{2Y^5}{2Y^5})^3\cdot(\frac{X^3}{2X^3})^3=

(2Y52Y5)3ā‹…(X32X3)3ā‹…(2Y32Y6)2ā‹…(X22X2)2= (\frac{2Y^5}{2Y^5})^3\cdot(\frac{X^3}{2X^3})^3\cdot(\frac{2Y^3}{2Y^6})^2\cdot(\frac{X^2}{2X^2})^2=


Advanced Level Power of a Power Exercises

(3X+7)Xā‹…(3X)3= (3^{X+7})^X\cdot(3^X)^3=

(2Xāˆ’2)Xā‹…(3Xāˆ’2)6= (2^{X-2})^X\cdot(3^{X-2})^6=

(3Xāˆ’3)Xā‹…(3Xāˆ’3)3= (3^{X-3})^X\cdot(3^{X-3})^3=

(32āˆ’3)2ā‹…(7Xāˆ’5)2= (3^{2-3})^2\cdot(7^{X-5})^2=

(8Xāˆ’3)Xā‹…(72X+2)X= (8^{X-3})^X\cdot(72^{X+2})^X=


Join Over 30,000 Students Excelling in Math!
Endless Practice, Expert Guidance - Elevate Your Math Skills Today
Test your knowledge

Review Questions

What is a power of a power?

A power of a power is an expression in which we raise a power to another power.

What is a power of a power and example?

A power of a power is a power in which the base is also a power, for example:

  • (32)5 \left(3^2\right)^5
  • (52x+1)2 \left(5^{2x+1}\right)^2

How do you calculate a power of a power?

To solve a power of a power, we must multiply the exponents, and the result of the multiplication is placed as the exponent on the initial base.


Exercises on Power of a Power

Exercise 1

Assignment

23Ɨ24+(43)2+2523= 2^3\times2^4+(4^3)^2+\frac{2^5}{2^3}=

Solution

23ā‹…24+(43)2+2523= 2^3\cdot2^4+\left(4^3\right)^2+\frac{2^5}{2^3}=

23+4+43ā‹…2+2(5āˆ’3)= 2^{3+4}+4^{3\cdot2}+2^{\left(5-3\right)}=

27+46+22 2^7+4^6+2^2

Answer

22+27+46 2^2+2^7+4^6


Do you know what the answer is?

Exercise 2

Assignment

(4x)y= (4^x)^y=

Solution

(4x)y=4xā‹…y \left(4^x\right)^y=4^{x\cdot y}

Answer

4xy 4^{xy}


Exercise 3

Assignment

(22)3+(33)4+(92)6= (2^2)^3+(3^3)^4+(9^2)^6=

Solution

We will use the formula

(am)n=amā‹…n \left(a^m\right)^n=a^{m\cdot n}

22ā‹…3+33ā‹…4ā‹…92ā‹…6= 2^{2\cdot3}+3^{3\cdot4}\cdot9^{2\cdot6}=

26+312ā‹…912 2^6+3^{12}\cdot9^{12}

Answer

26+312+912 2^6+3^{12}+9^{12}


Check your understanding

Exercise 4

Assignment

(42)3+(g3)4= (4^2)^3+(g^3)^4=

Solution

We will use the formula

(am)n=amā‹…n \left(a^m\right)^n=a^{m\cdot n}

42ā‹…3+93ā‹…4= 4^{2\cdot3}+9^{3\cdot4}=

46+912 4^6+9^{12}

Answer

46+912 4^6+9^{12}


Exercise 5

Assignment

((7Ɨ3)2)6+(3āˆ’1)3Ɨ(23)4= ((7\times3)^2)^6+(3^{-1})^3\times(2^3)^4=

Solution

We will use the formula

(am)n=amā‹…n \left(a^m\right)^n=a^{m\cdot n}

(7ā‹…3)2ā‹…6+3āˆ’1ā‹…3ā‹…23ā‹…4= (7\cdot3)^{2\cdot6}+3^{-1\cdot3}\cdot2^{3\cdot4}=

2112+3āˆ’3ā‹…212 21^{12}+3^{-3}\cdot2^{12}

Answer

2112+3āˆ’3ā‹…212 21^{12}+3^{-3}\cdot2^{12}


Do you think you will be able to solve it?

Examples with solutions for Power of a Power

Exercise #1

Insert the corresponding expression:

(85)10= \left(8^5\right)^{10}=

Video Solution

Step-by-Step Solution

To simplify the expression (85)10\left(8^5\right)^{10}, we'll apply the power of a power rule for exponents.

  • Step 1: Identify the given expression.
  • Step 2: Apply the power of a power rule, which states that (am)n=amā‹…n(a^m)^n = a^{m \cdot n}.
  • Step 3: Multiply the exponents to simplify the expression.

Now, let's work through each step:
Step 1: The expression given is (85)10\left(8^5\right)^{10}.
Step 2: We will use the power of a power rule: (am)n=amā‹…n(a^m)^n = a^{m \cdot n}.
Step 3: Multiply the exponents: 5ā‹…10=505 \cdot 10 = 50.

Thus, the expression simplifies to 8508^{50}.

The correct simplified form of the expression (85)10\left(8^5\right)^{10} is 8508^{50}, which corresponds to choice 2.

Alternative choices:

  • Choice 1: 8158^{15} is incorrect because it misapplies the exponent multiplication.
  • Choice 3: 858^5 is incorrect because it does not apply the power of a power rule.
  • Choice 4: 828^2 is incorrect and unrelated to the operation.

I am confident in the correctness of this solution.

Answer

850 8^{50}

Exercise #2

(35)4= (3^5)^4=

Video Solution

Step-by-Step Solution

To solve the exercise we use the power property:(an)m=anā‹…m (a^n)^m=a^{n\cdot m}

We use the property with our exercise and solve:

(35)4=35Ɨ4=320 (3^5)^4=3^{5\times4}=3^{20}

Answer

320 3^{20}

Exercise #3

Insert the corresponding expression:

(166)7= \left(16^6\right)^7=

Video Solution

Step-by-Step Solution

To solve the expression (166)7(16^6)^7, we will use the power of a power rule for exponents. This rule states that when you raise a power to another power, you multiply the exponents. Here are the steps:

  • Identify the components: The base is 16, and the inner exponent is 6. The outer exponent is 7.
  • Apply the power of a power rule: According to the rule, (am)n=amā‹…n(a^m)^n = a^{m \cdot n}. Thus, (166)7=166ā‹…7(16^6)^7 = 16^{6 \cdot 7}.
  • Multiply the exponents: Calculate the product of the exponents 6Ɨ76 \times 7. This gives us 42.
  • Rewrite the expression: Substitute the product back into the expression, giving us 164216^{42}.

Therefore, the simplified expression is 1642\mathbf{16^{42}}.

Checking against the answer choices, we find:
1. 164216^{42} is given as choice 1.
2. Other choices do not match the simplified expression.
Choice 1 is correct because it accurately reflects the application of exponent rules.

Consequently, we conclude that the correct solution is 1642\mathbf{16^{42}}.

Answer

1642 16^{42}

Exercise #4

Insert the corresponding expression:

(45)2= \left(4^5\right)^2=

Video Solution

Step-by-Step Solution

To solve this problem, let's carefully follow these steps:

  • Step 1: Identify the base and exponents in the expression.
  • Step 2: Use the power of a power rule to simplify the expression.
  • Step 3: Choose the appropriate option from the given answer choices.

Now, let's break this down:

Step 1: The expression given is (45)2(4^5)^2. Here, the base is 4, the inner exponent is 5, and the outer exponent is 2.

Step 2: We apply the power of a power rule for exponents, which states that (am)n=amā‹…n(a^m)^n = a^{m \cdot n}.

Using the rule, we have:

(45)2=45ā‹…2=410 (4^5)^2 = 4^{5 \cdot 2} = 4^{10}

This means the expression (45)2(4^5)^2 can be simplified to 4104^{10}.

Step 3: From the answer choices provided, we need to select the one corresponding to 45ā‹…24^{5 \cdot 2}:

  • Choice 1: 4254^{\frac{2}{5}} - This is incorrect because it deals with division of exponents and not multiplication.
  • Choice 2: 45āˆ’24^{5-2} - This is incorrect as it incorrectly subtracts the exponents.
  • Choice 3: 45Ɨ24^{5 \times 2} - This is the correct choice.
  • Choice 4: 45+24^{5+2} - This is incorrect as it incorrectly adds the exponents.

Therefore, the solution to the problem is 45Ɨ2=4104^{5 \times 2} = 4^{10}, which corresponds to choice 3.

Answer

45Ɨ2 4^{5\times2}

Exercise #5

Insert the corresponding expression:

(27)5= \left(2^7\right)^5=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the given information.
  • Step 2: Apply the appropriate exponent rule.
  • Step 3: Perform the necessary calculations.

Let's work through each step:

Step 1: The given expression is (27)5 \left(2^7\right)^5 . Here, the base is 2 2 , and we have two exponents: 7 7 in the inner expression and 5 5 outside.

Step 2: We'll use the power of a power rule for exponents, which states (am)n=amā‹…n (a^m)^n = a^{m \cdot n} . This means we will multiply the exponents 7 7 and 5 5 .

Step 3: Calculating, we multiply the exponents:
7Ɨ5=35 7 \times 5 = 35

Therefore, the expression (27)5 \left(2^7\right)^5 simplifies to 235 2^{35} .

Now, let's verify with the given answer choices:

  • Choice 1: 212 2^{12} - Incorrect, as the exponents were not multiplied properly.
  • Choice 2: 22 2^2 - Incorrect, as it significantly underestimates the combined exponent value.
  • Choice 3: 235 2^{35} - Correct, matches the calculated exponent.
  • Choice 4: 257 2^{\frac{5}{7}} - Incorrect, involves incorrect fraction of exponents.

Thus, the correct choice is Choice 3: 235 2^{35} .

I am confident in the correctness of this solution as it directly applies well-established exponent rules.

Answer

235 2^{35}

Start practice